Enhancing Tourism Destination Promotion through Strategic Instagram Engagement: A Case Study of @visitkarangsambung - Nurdin Hidayah; Herlan Suherlan; R. Fajar Widiarrachman; Rifki Rahmanda Putra; Fitra Ananta Sujawoto (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
This study explores the performance of the Instagram account @visitkarangsambung using the Circular Model of SOME (Share, Optimize, Manage, Engage). Employing a qualitative case study approach, the research reveals that current management practices are suboptimal in all four model dimensions. Key issues include unstructured content sharing, limited audience interaction, weak content management, and lack of strategic engagement. Findings offer actionable insights for improving Instagram engagement and contribute to the literature on social media marketing in rural tourism. The implications of this study provide input for organizations that want to increase Instagram engagement rates, namely: strengthening share strategy; optimizing content performance; better content management; and more active engagement strategies. This research aims to contribute to the existing literature on social media marketing in tourism and fill the gap on tourism village social media marketing research.